Transient natural convection double diffusion from a heated cylinder buried in a saturated porous medium - Camargo, José Rui; Macedo, Amilcar Gomes; Chaves, Carlos Alberto; Chaves, José Camilo; Trevisan, Osvair Vidal (Revista Ciências Exatas, 2008)
In this work numerical solutions are presented for the transient natural convection heat transfer by double diffusion from a heated cylinder buried in a saturated porous medium where both the cylinder and the medium surfaces are maintained at constant uniform temperature and concentration. The governing equations are expressed in bicylindrical coordinates in the stream function formulation and handled numerically by a control-volume method. Heat and Mass Transfer are studied as a function of Rayleight number, Lewis number and the buoyancy ratio number.